Prevalence and severity of anxiety and depression in Chinese patients with breast cancer: a systematic review and meta-analysis - Tao, Fuying; Xu, Mengnan; Zou, Qi; Tang, Lin; Feng, Jianping; Li, Zhenyu (Frontiers in Psychiatry, 2023)
Abstract Context. Anxiety/depression in breast cancer (BC) is common around the world, and Chinese BC patients should not be ignored. The prevalence of anxiety and depression among BC patients are various in different regions of China, but no clear summarization has been made. Purpose. This meta-analysis aimed to evaluate the prevalence and severity of anxiety and depression among breast cancer (BC) patients in China. Methods. A literature search on PubMed, Web of Science, Embase, CINAHL, Scopus, PsycINFO, Cochrane database library, CNKI, Wanfang and SinoMed was conducted up to 29 December 2021. The effect size (ES) or standard mean difference (SMD) and the corresponding 95% confidence intervals (CIs) for the prevalence and severity of anxiety/depression were calculated using the STATA 12.0 software. Results. A total of 63 identified studies were included, containing a total of 53513 Chinese women confirmed breast cancer. The results showed a high pooled prevalence of anxiety (38%, 95% CI, 27%-50%, I2=99.4%, P<0.001) and depression (38%, 95% CI, 33%-44%, I2=99.2%, P<0.001) among Chinese BC patients. Moreover, both anxiety (SMD=0.30, 95%CI, 0.08-0.53, I2=91.6%, p<0.001) and depression (SMD=0.25, 95%CI, -0.05-0.55, I2=95.3%, p<0.001) in BC patients were more serious than those in healthy controls, but not significantly different from patients with other diseases. Specifically, among the 6 regions included, the prevalence of anxiety and depression were both the highest in Northeast China, obviously superior than the second-highest region. Conclusion. The study showed high levels of anxiety and depression among BC patients in China, especially those in the northeast. Clinicians and researchers should pay attention to the psychological problems of patients with breast cancer and regard it as one of the important prognostic outcomes of patients.